Monitoramento de reações adversas em pacientes chagásicos tratados com benzonidazol - Pontes, Vania Maria Oliveira de (2007)
Chagas’ disease, caused by protozoan Trypanosoma cruzi, still represents one of the most important endemics diseases in American continent and has been diagnosed from south of United States to South of Argentina. In Brazil, benznidazole is the only drug currently available for specific treatment of this disease, but its safe clinical application demands attention for causing adverse reactions, mainly in adults patients. OBJECTIVE: To monitor the occurrence of adverse reactions in chagasic patients treated with benznidazole in Fortaleza, Ceará. METHODOLOGY: Descriptive longitudinal prospective study of evaluation of adverse reactions occurrence during chagasic patient treatment with benznidazole. Thirty two chronics chagasic patients were included in the study since january of 2005 to june of 2006. Data were collected through questionnaire, interview and laboratorial exams results interpretation. Blood samples were collected before, during (30 days) and after treatment with benznidazole (60 days). Biochemical, hematological and serologic tests were made. The suspects Adverse Drug Reactions (ADR) were appraised for Ceará Pharmacovigilance Centre (CEFACE). In the statistical analysis were used the SPSS 13.0 and t - Student test, considering the significance level p < 0,05. RESULTS: Twenty signs and symptoms were recorded by 28 (87,5%) patients. The most frequent symptoms were: Pruritus (57%), paresthesia (46%) and headache (46%). Most of reactions were classified according to causality and severity as probable (60,7%) and slight (73%), respectively. Of the 28 patients that presented undesirable effects, 8 (29%) had treatment withdrew and the most frequent reactions were paresthesia (87,5%) and cutaneous rash (62,5%). In relation to laboratorial tests, the alteration most meaningful was eosinophylia in 6 (18%) patients. Although not significant, there was an expressive increase of the values of the transaminases levels in 3 (9,4%) patients. After treatment, the majority of symptoms and laboratorial tests results returned to the previous levels prior to medication. CONCLUSION: Adverse reactions are frequent in patients treated with benznidazole. Clinical pharmacists can help patients to deal with these problems contributing for better therapeutic results. Keywords: Chagas Disease – Therapy; Benzonidazole; Trypanosomicides - adverse effects.